Fundamental Improvement of Creep Resistance of New-Generation Nano-Oxide Strengthened Alloys via Hot Rotary Swaging Consolidation - Svoboda, Jiří; Kunčická, Lenka; Luptáková, Natália; Weiser, Adam; Dymáček, Petr (Materials (Basel, Switzerland), 2020)
New-generation oxide dispersion-strengthened (ODS) alloys with a high volume fraction of nano-oxides of 5% are intended to become the leading creep- and oxidation-resistant alloys for applications at 1100-1300 °C. Hot consolidation of mechanically alloyed powders by intensive plastic deformation followed by heat treatment of the alloys are the key aspects for achieving top creep properties, typically ensured by a coarse-grained microstructure strengthened with homogeneously dispersed, very stable yttrium nano-oxides. The rotary swaging method proves to be favourable for hot consolidation of the new-generation ODS alloy presented. Compared to specimens consolidated by hot rolling, consolidation by hot rotary swaging predetermines the formation of coarse grains with a very high aspect ratio during subsequent secondary recrystallization. Such a grain morphology increases the creep strength of the new-generation ODS alloy considerably.
Keywords: powder hot consolidation; rotary swaging; rolling; mechanical alloying; oxide dispersion strengthened (ODS) alloy